From what we know to what we do: translating stroke rehabilitation research into practice. Issue 1 (24th December 2012) - Walker, Marion F.; Fisher, Rebecca J.; Korner‐Bitensky, Nicol; McCluskey, Annie; Carey, Leeanne M.
<x xml:space="preserve">Abstract</x> Despite the recent advances in stroke rehabilitation research, the translation of research evidence into practice remains a challenge. The purpose of this article is to communicate practical experience and describe research methodologies used to promote change and implementation of stroke rehabilitation research in three international settings. In England, the development of an evidence‐based consensus document, combined with qualitative and quantitative methods, was used to promote practice change in community‐based stroke services. The Canadian research program involved synthesis of evidence, creation of user friendly information, and development of multimodal knowledge transfer strategies to promote change at an individual clinician level. Australian researchers followed a multistep process, involving audit and feedback, identification of barriers, and tailored education to improve implementation of one clinical guideline recommendation. Reducing the evidence–practice gap requires the development of active management strategies. This article highlights the importance of close collaboration between stakeholders – both in terms of the transfer of evidence into clinical practice and for optimizing future Phase IV implementation research endeavours.